Modelo de enseñanza-aprendizaje centrado en la resolución de problemas: fundamentación, presentación e implicaciones educativas - Lopes, J. Bernardino; Costa, N. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
The present article seeks to present a Science Teaching and Learning Model Based on Problem Solving. The presentation is based on a review or related Literature. An empirical study carried out in Portugal with secondary school teachers of Physics and Chemistry also contributed do devising the model. Finally, the implications for education and further research arising from the model in question are referred to.